Uso da curcumina, tanino, azul de metileno e azul de toluidina como fotossensibilizador, na terapia fotodinâmica contra o enterococcus faecalis: estudo in vitro - Braz, Maria Cleide Azevedo (2019)
The objective of this study was to evaluate the microbial reduction after Photodynamic Therapy (AAAAAPDT) as an adjuvant to Mechanical Chemical Preparation (PQM), using 0.005% Methylene Blue, 0.005% Toluidine Blue, 0.005% Hydrolyzable Tannin and Curcumin to 0.005% in root canals of human teeth, lower incisors, single channel, contaminated with Enterococcus faecalis. We used 120 teeth, divided into six groups, 20 specimens in each group. Group 1, where only PQM was performed with 2.5% NaOCl as irrigation solution, group 2, PQM and irrigation with Physiological Serum, in group 3, PQM and irrigation with 2.5% NAOCl and Photodynamic Therapy (AAAAAPDT) with methylene blue as photosensitizer, group 4, PQM and irrigation with 2.5% NAOC1 and Toluidine blue AAAAAPDT as photosensitizer, group 5, PQM with 2.5% NAOCL as irrigation solution and AAAAAPDT with Tannin as a photosensitizer and in group 6 PQM with 2.5% NAOCL as irrigation solution and AAAAAPDT with Curcumin as photosensitizer. For the AAAAAPDT, 1 ml of 0.005% photosensitizer that remained inside the root canal for 5 min was used. For the irradiation, a portable semiconductor laser (Laser DUO®, GaAlAs, InGaAlP) was used, wavelength of 660 nm, power of 100 mW, totaling 1.8 J of energy and irradiation time of 180 s. And for group 6 the light used was a LED light from Gnatus®. The microbiological collection was done before the PQM, after the PQM and after 48 hours of the PQM, that is, the microbiological samples were denominated initial, intermediate and final. Initial and Intermediate collection the CFU count was performed 48 hours after the collection and final collection with 7 days after collection. The Amostral Calculus was performed and, in the intergroup analysis, a significant difference was observed in the number of CFU at the initial time (p <0.001) and in the final moment (p <0.001). In the intragroup evaluation, it was found that the number of CFU showed a significant decline trend for G4 (p = 0.007) and G5 (p = 0.001). When comparing the initial and final values, the percentage reductions in relation to the average CFU for G4 and G5 were, respectively, 68.2% and 69.9%. According to the statistical data, groups G4 and G5 had percentages of reduction of CFU equivalents, but G5 (group with Tannin), showed a better result in relation to the lethal effect against Enterococcus Faecalis.